Occupational Health Safety, Motivation and Discipline Program to Improve Company Employee Performance in Tarakan City - Cahyaningrum, Widyastuti; Wahyuni, Sri (Indonesian Journal of Advanced Research, 2023)
This research aims to prove the influence of occupational safety and health, motivation and discipline on employee performance in Tarakan City companies. This research uses a quantitative approach with survey methods and data collection by distributing questionnaires. In this research, a probability sampling technique with simple random sampling was used. Measurements in this questionnaire use a Likert scale of 5 to 1. The population in this study was 304 employees with a total sample of 135 respondents. The data analysis method used in this research is multiple linear regression and t test. The results of this research prove that Occupational Health and Safety has a positive and significant effect on employee performance, motivation has a positive and significant effect on employee performance, and discipline has a positive and significant effect on employee performance.